Ascites - Román Vargas, Rossana (2007)
Ascites is the abnormal accumulation of ﬂuid into the peritoneal cavity, which in the cirrhotic patient is due to a number of determinant factors. Many theories have been elaborated in that regard during the previous decades, however the current concept states that the chief pathophysiologic mechamism of ascites formation is a permanent state of peripheral vasodilation in the cirrhotic patient, associated with a relative renal hypoperfusion, which in turn activates a host of sodium and water retaining mechanisms. It is a progressive phenomenon and its natural history can be viewed as a spectrum of disease, having at one end of the spectrum the so called hepatorenal syndrome, with ascites refractory to diuretic treatment and a higher frequency of bacterial colonization of the ascitic ﬂuid, so called spontaneous bacterial peritonitis. This article reviews the pathophysiology, diagnosis, complications and therapeutic aspects of ascites in the cirrhotic patient.